Prospects for the development of electronic commerce in Russia in the conditions of digital economy - E. O. Vostrikova; A. P. Meshkova (Новые технологии)
E-commerce is a form of running business using information and communication technologies. E-commerce objects include not only traditional types of services and goods, but also informational ones. In general, the trends in e-commerce development in Russia can be regarded as positive. The ongoing coronavirus pandemic affects everything, including spending money and interaction of firms in the marketplace. Current trends indicate an acceleration in digitalization, both in the private and public sectors. Therefore, in the future, only the online seller will have success whose business will be digitized and optimized as much as possible. At the same time, the transition of firms and consumers to the electronic segment is associated with certain costs and risks. This aspect requires serious attention from both academic economists and authorities; competent, but not excessive, intervention is required. In this article, the authors reveal both the positive and negative aspects of running e-business from the point of view of sellers and buyers, and also offer their own views on the e-commerce market development in the context of mass digitalization accelerated due to the coronavirus crisis. Provided that the rate of Internet penetration in the regions remains at the same level, e-commerce in Russia will be able to maintain the current growth rate and realize its potential as an important trading platform for both domestic and foreign economic agents.